Analysis Of The Level Of Primigravida Anxiety In Facing The Labor Process In Terms Of Education On The Labor Process In The Room Maternity Clinic Pratama Eka Medika, Mojosari – Mojokerto - Rahma Fauziyah; Widya Anggraeni (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
The psychological condition of the mother before giving birth is often underestimated and ignored, even though a good psychological condition is certainly very influential on the mother's confidence and the mother's enthusiasm to give birth to a healthy baby. and in a safe way. The mother's mental state that affects the mother's anxiety level during labor can be caused by several factors, including lack of knowledge and information about the correct labor process and the implementation of complete necessary training. Health workers also have a significant influence on the anxiety levels of first-time mothers. The purpose of this study was to analyze the level of primigravida anxiety in facing the labor process in terms of childbirth education in the delivery room of Fakfak Hospital West Papua. The research design used was Pre-Experimental with One Group Pretest-Posttest research design. The population in this study was all primigravida mothers who came to check at the Gynecology Poly of FakFak Hospital West Papua. The sampling technique used was consecutive sampling and obtained a sample of 35 respondents. The independent variable in this study was labor education. The variable tied to this study was the level of primigravida anxiety in the face of labor. Data analysis using Wilcoxon statistical test. The results showed primigravida anxiety levels before being given treatment were mostly moderate anxiety levels as many as 19 respondents (54.3%), mild anxiety 12 respondents (34.3%) and severe anxiety as many as 4 respondents (11.4%). While the level of primigravida anxiety after being given treatment or intervention in the form of education about the labor process, the results obtained were almost half the anxiety levels of respondents had mild anxiety levels as many as 17 respondents (48.6%), not anxious as 11 respondents (31.4%), and 7 respondents (20%) experienced moderate anxiety levels. Wilcoxon Asymp statistical test results. Sig. (2-tayled) is 0.000 < 0.05, so it can be implied that "Ha is accepted".meaning there is a difference in the level of anxiety before treatment and after treatment.